Direct coupling of size exclusion chromatography and mass spectrometry for the characterization of complex monoclonal antibody products. Issue 12 (28th March 2022) - Murisier, Amarande; Andrie, Marie; Fekete, Szabolcs; Lauber, Matthew; D'Atri, Valentina; Iwan, Katharina; Guillarme, Davy
Abstract : The present study describes the possibilities offered by an innovative bioinert size exclusion chromatography column for size variant characterization of complex monoclonal antibody products. This size exclusion chromatography column includes a novel column hardware surface. The column was prepared from metallic hardware components that were treated to have prototype hydrophilically modified hybrid organic–inorganic silica surfaces called hybrid surface technology. This provides a significant reduction in nondesired hydrophobic and electrostatic interactions that can occur between column and analyte when performing size exclusion chromatography analysis with volatile mobile phase. Compared to a reference stainless‐steel column packed with the same batch of packing material, peak tailing, band broadening, and above all recovery of high molecular weight species were distinctly improved for all types of monoclonal antibody products. Based on our observations, we found that 50 mM ammonium acetate in water was a suitable mobile phase offering good compromise in terms of liquid chromatography performance and mass spectrometry sensitivity. In addition, method repeatability (intra‐ and interday relative standard deviations) on elution times and high molecular weight species peak areas were found to be excellent. By using this innovative size exclusion chromatography material, the low and high molecular weight species contained in various stressed and nonstressed monoclonal antibody products were successfully characterized with mass spectrometry detection.